Investigating discrepancies in program quality related to youth volleyball athletes' needs support. (September 2016) - Bean, Corliss; Forneris, Tanya; Brunet, Jennifer
Abstract: Program quality has been outlined as an important predictor of positive outcomes in youth development programs; however, little evidence exists to support this, particularly within sport. Objective: The purpose of this study was to examine the associations between researcher- and coach-assessed program quality scores as they relate to youth volleyball athletes' basic needs support. Design: Observational data and self-report data were gathered from coaches and youth. Researchers completed 84 observations using a measure of program quality across 14 teams. Coaches completed the same measure at the end of the season and 138 athletes ( M age  = 14.50) from the 14 teams completed a self-report questionnaire pertaining to needs support. Data were analyzed using polynomial regressions with response surface methodology. Results: Athletes' needs support was significantly ( p  < 0.001) associated with all domains of researcher- and coach-assessed program quality (i.e., safe environment, supportive environment, interaction, engagement), and between 20 and 35% of the variance in athletes' needs support was explained by these variables. The degree of discrepancy between researcher- and coach-assessed program quality increased when progressing through three domains of program quality (safe environment, supportive environment, engagement). Response surface methods indicated that as the degree of agreement increased between researchers' and coaches' ratings of the safety of the environment, supportiveness of the environment, and opportunities for engagement, so did athletes' basic needs support scores in a linear fashion. Conclusions: Practical implications surrounding coach education and the importance of knowledge translation between academics and practitioners are noted, and future research directions are discussed. Highlights: Program quality was examined in relation to youth athletes' needs support. Polynomial regression with response surface analysis was used to analyze the data. All domains of program quality predicted youth athletes' needs support. Discrepancies existed between researcher and coach assessments of program quality.